Synthesis and characterization of phosphonate and aromatic-based polynorbornene polymers derived from the ring opening metathesis polymerization method and investigation of their thermal properties - Isiksel, E.; Kahraman, G.; Suer, N. Ceren; Wang, D. -Y.; Eren, T. (WILEY, 2019)
In the present study, phosphonate ester, phosphonic acid, and aromatic (phenyl, naphthalene, anthracene) groups containing polymers were synthesized by the ROMP method to analyze thermal properties of these polymers. Thermal stability of the synthesized polymers is tested by thermal gravimetric analysis under nitrogen, air, and microscale combustion calorimetry analysis. Analysis shows that thermal behavior is directly related to the phosphorus level in the copolymer series. All the polymers are thermally stable under nitrogen and air up to 900 degrees C. Synergistic charring effect under air was observed between aromatic groups and phosphonic acid functionality in the copolymer series. Anthracene units have a greater potential to form carbonaceous char than the naphthalene and phenyl units. Phosphonate ester and naphthalene units bearing copolymers (P3A) gave 8.13% char yield at 900 degrees C under air. Phosphonic acid derivatives of this polymer, P3D, gave a highest char residue of 17.15% under the same condition. The introduction of phosphonate and phosphonic acid in each copolymer series is also beneficial in reducing the peak heat release rate (PHRR). Cleavage of the phosphonate ester bearing homopolymer (P4) to phosphonic acid (P4A) causes a sharp decrease in the PHRR ratio from 274 to 28.2 W/g. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47085.
Keywords: aromaticity; copolymer; flame retardancy; inflammable; phosphonate ester; phosphonic acid; ROMP; FREE FLAME RETARDANTS; COPOLYMERS; POLYPHOSPHONATES; PERFORMANCE; POLYESTER; Polymer Science